A quite sensitive fluorescent loop-mediated isothermal amplification for rapid detection of respiratory syncytial virus - Yihong Hu; Zhenzhou Wan; Yonglin Mu; Yi Zhou; Jia Liu; Ke Lan; Chiyu Zhang (Journal of Infection in Developing Countries)
Introduction: Human respiratory syncytial virus (hRSV) is a common respiratory virus closely related to respiratory tract infection (RTI). Rapid and accurate detection of hRSV is urgently needed to reduce the high morbidity and mortality due to hRSV infection.